Vietnam country brief - Harris, Jody; Huynh, Phuong; Nguyen, Hoa T.; Hoang, Nga; Tran, Lan Mai; Tuyen, Le Danh; Nguyen, Phuong Hong (Transform Nutrition, 2020)
Vietnam has achieved significant progress in reducing undernutrition over the past several decades, but ethnic minority groups are being systematically left behind and this is limiting progress on national reductions. The Vietnam Story of Change in Nutrition study aims to understand the history, contemporary treatment, and future of nutrition in Vietnam, including policy and practice in relation to undernutrition with a focus on equity for Vietnam’s 53 ethnic minority groups. This brief aims to highlight the main findings and give recommendations on how to tackle the remaining pockets of high malnutrition in Vietnam.